2015
DOI: 10.1111/gcb.13052
|View full text |Cite
|
Sign up to set email alerts
|

Climate change alters plant biogeography in Mediterranean prairies along the West Coast, USA

Abstract: Projected changes in climate are expected to have widespread effects on plant community composition and diversity in coming decades. However, multisite, multifactor climate manipulation studies that have examined whether observed responses are regionally consistent and whether multiple climate perturbations are interdependent are rare. Using such an experiment, we quantified how warming and increased precipitation intensity affect the relative dominance of plant functional groups and diversity across a broad c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 53 publications
(99 reference statements)
1
38
0
Order By: Relevance
“…However, some other studies have found the direct negative effects of droughts on native annual diversity to outweigh the positive indirect ones (Tilman and Haddi , Pfeifer‐Meister et al. ). One possible explanation of this discrepancy is that our site underwent a longer‐term trend toward drier winters during the 12 yr preceding the drought, which was associated with trends toward lower forb diversity and a lesser prevalence of drought‐intolerant species (Harrison et al.…”
Section: Discussionmentioning
confidence: 95%
“…However, some other studies have found the direct negative effects of droughts on native annual diversity to outweigh the positive indirect ones (Tilman and Haddi , Pfeifer‐Meister et al. ). One possible explanation of this discrepancy is that our site underwent a longer‐term trend toward drier winters during the 12 yr preceding the drought, which was associated with trends toward lower forb diversity and a lesser prevalence of drought‐intolerant species (Harrison et al.…”
Section: Discussionmentioning
confidence: 95%
“…The southern site is in the Klamath‐Siskiyou ecoregion of southwestern Oregon, the central site is at the southern end of the Willamette Valley ecoregion in western Oregon, and the northern site is in the Puget Trough ecoregion of central‐western Washington (U.S. EPA [Environmental Protection Agency], ). There is a strong climate gradient from north to south, with the northern site experiencing the coolest mean annual temperatures and most mesic summer soil moistures, the central site experiencing intermediate temperatures and soil moisture, and the southern site experiencing the warmest mean annual temperatures and driest soils in the summer (Pfeifer‐Meister et al, ) (Supporting Information Table , Figure ).…”
Section: Methodsmentioning
confidence: 99%
“…At each site, 20 circular plots (7.1 m 2 ) were randomly assigned to one of four climate treatments with five replicates each: control (ambient temperature and precipitation), warming (canopy temperature raised by 2.5°C), warming with additional precipitation (warming + ppt; plots irrigated to fully offset a warming‐induced drying effect), and drought (annual precipitation reduced by 40%). The southern and central sites were part of a previous experiment from 2010–2012 with a different set of treatments consisting of control, warming by 2.5°C, increased precipitation intensity by 20%, and warming by 2.5°C + increased precipitation intensity by 20% (Pfeifer‐Meister et al, ; Reynolds, Johnson, Pfeifer‐Meister, & Bridgham, ). However, the precipitation intensity treatments had almost no effect on either plant or ecosystem responses since most of the additional water was applied during the wet season (Pfeifer‐Meister et al, ; Reynolds et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations